Broadband Plasmon Waveguide Resonance Spectroscopy for Probing Biological Thin Films - ZHANG, HAN (2009)
A commercially available spectrometer has been modified to perform plasmon waveguide resonance (PWR) spectroscopy over a broad spectral bandwidth. When compared to surface plasmon resonance (SPR), PWR has the advantage of allowing measurements in both s- and p-polarizations on a waveguide surface that is silica or glass rather than a noble metal. Here the waveguide is a BK7 glass slide coated with silver and silica layers. The resonance wavelength is sensitive to the optical thickness of the medium adjacent to the silica layer. The sensitivity of this technique is characterized and compared with broadband SPR both experimentally and theoretically. The sensitivity of spectral PWR is comparable to that of spectral SPR for samples with refractive indices close to that of water. The hydrophilic surface of the waveguide allows supported lipid bilayers to be formed spontaneously by vesicle fusion; in contrast, the surface of an SPR chip requires chemical modification to create a supported lipid membrane. Broadband PWR spectroscopy should be a useful technique to study biointerfaces, including ligand binding to transmembrane receptors and adsorption of peripheral proteins on ligand-bearing membranes.